Investigating the mechanical and optical properties of novel Urethandimethacrylate (UDMA) and Urethanmethacrylate (UMA) based rapid prototyping materials. Issue 10 (October 2021) - Rosentritt, Martin; Huber, Christina; Strasser, Thomas; Schmid, Alois
Graphical abstract: Highlights: UDMA/UMA based materials deliver promising performance for occlusal splint applications. The addition of UMA monomers increases flexibility of UDMA based rapid prototyping materials. UMA content of up to 25% seems clinically appropriable. Optimal UMA content should be subject to further investigations. Abstract: Objective: This study is focused on testing experimental rapid prototyping materials for occlusal splints made from Urethandimethacrylate (UDMA) and Urethanmethacrylate (UMA). Methods: Materials were mixed from UDMA and UMA in ratios of 1.0:0.0, 0.75:0.25, 0.5:0.5, 0.25:0.75 and 0.0:1.0. Specimens were printed using digital light processing (DLP). After post-processing, the specimens underwent testing on flexural strength, modulus of elasticity, hardness, wear behavior, surface roughness, gloss and color stability. All tests were performed after 24 h (baseline) and 10 days of water storage (aging). Splints underwent cyclic pull-off and insertion testing, which was alongside simulated using finite element analysis. Results: The mechanical properties were significantly influenced by changes in the UDMA:UMA ratio. Statistical analysis revealed that increased amounts of UMA correlated with a decrease in flexural strength (92.0 to 30.7 MPa), modulus of elasticity (2.4 to 0.6 GPa), hardness (155.1 to 102.0 N/mm 2 ) and wear resistance (−1394.9 to −1742.1 μm). Materials with higher amounts of UMA were also more likely to be influenced by water storage. Specimens with 75% and 100% UMA content were partly not analyzable due to soft consistency. Optical properties showed only minor influence from UMA content and aging. Differences in surface roughness (3.9 to 2.4 μm) and color stability were insignificant. Gloss was partly influenced by the UDMA:UMA ratio and water storage. Mean survival rates for cyclic pull-off and insertion testing ranged from 2537 to 23, 857 cycles. A correlation between the amount of UMA and survival rates was observed. Significance: The addition of up to 25% UMA showed promising results, complying with clinical standards and delivering acceptable results in the cyclic pull-off and insertion test. Further investigation on increments between 0 and 25% UMA could help to find an optimum.